AKTUALISASI BELA NEGARA MELALUI REFORMASI PELAYANAN PUBLIK DI SEKTOR PERHUBUNGAN DI PROVINSI SULAWESI TENGGARA - Maudhy Satyadharma; Rina Sutriana; Sylsiani Mursalim; Barmuddin Barmuddin (PPM Sdirjianbang Akademi Militer, 2026)
This study analyzes the actualization of national defense through public service reform in the transportation sector in Southeast Sulawesi Province. National defense is understood as a non-military responsibility manifested through the professionalism, integrity, and dedication of state civil servants in providing fair, safe, and inclusive transportation services. The research method used a descriptive qualitative approach with data from interviews, observations, literature, and policy documents. The results of the study indicate that the digitalization of services, improved safety, strengthened civil service integrity, and expanded regional connectivity strengthen public trust and social cohesion. Transportation service reform not only increases efficiency but also serves as a non-military national resilience strategy that affirms the state's presence for all communities, including those in remote areas of Southeast Sulawesi Province.